2012
DOI: 10.1007/s00296-012-2531-0
|View full text |Cite
|
Sign up to set email alerts
|

Markers of acute neuropsychiatric systemic lupus erythematosus: a multidisciplinary evaluation

Abstract: This study was aimed to assess: (1) the additive diagnostic utility of diffusion-weighted imaging (DWI) and magnetic resonance angiography (MRA) over conventional MRI in detecting brain lesions in patients with acute primary neuropsychiatric systemic lupus erythematosus (NPSLE), and (2) the relevance of their findings to the associated NP manifestations. Included were 34 patients with acute NPSLE with mean age of 33.26 ± 10.14 years and duration of illness of 3.33 ± 1.71 years. Clinical interviewing and psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In our study, MRI abnormalities have been shown to be associated with cumulative organ damage in line with other studies that have found an association between the cumulative damage of SLE and the time of disease progression with white matter lesions [43,44]. Abda et al [45] demonstrated MRI abnormalities in older NPSLE patients with longer disease duration. Additional associations have been reported between WMH and cognitive dysfunction [39,43,46], cerebrovascular disease [43], low complement (CH50) level [39], and aPL antibodies [46].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, MRI abnormalities have been shown to be associated with cumulative organ damage in line with other studies that have found an association between the cumulative damage of SLE and the time of disease progression with white matter lesions [43,44]. Abda et al [45] demonstrated MRI abnormalities in older NPSLE patients with longer disease duration. Additional associations have been reported between WMH and cognitive dysfunction [39,43,46], cerebrovascular disease [43], low complement (CH50) level [39], and aPL antibodies [46].…”
Section: Discussionsupporting
confidence: 91%
“…More than half of the included studies were cohort studies and n = 9 were case–control ( n = 2 APS/aPL positive, n = 3 SLE, n = 4 NPSLE) [ 20–29 ]. Three studies were longitudinal in design [ 30 , 31 , 23 ] and at least seven studies were reported as retrospective where patient cohorts and data were extracted from case notes and patient-held registries [ 32 , 33 , 34 , 35 , 36 , 27 , 28 ]. Cohort sizes within studies were generally small with the exception of the two most recent included studies [ 30 , 37 ], with mean age ranging from 31 to 81 years, and >75% were female.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining other 13 studies included patients with aPL positivity and only one of these studies [ 25 ] reported that the presence of aPL was recorded at least twice over 12 weeks apart, whereas all other studies [ 30 , 37 , 33 , 34 , 39 , 40 , 36 , 23 , 24 , 26 , 27 , 29 ] recorded the presence of aPL following a single sample and did not specify that aPL was retested to confirm persistence. A small number of studies included all three criteria aPL (LA; IgG and IgM aCL; and anti-β2GPI) [ 32 , 20–22 , 24 , 25 ], with the combination aCL and LA as the most common included antibodies [ 38 , 34 , 35 , 36 , 28 , 29 ] or aCL as the only included aPL [ 37 , 33 , 31 , 26 , 27 ]. Only five studies indicated their cut-off values for aPL [ 32 , 33 , 37 , 38 , 24 ], with two of these studies using the Sapporo/Sydney laboratory criteria [ 38 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Today, several advanced imaging modalities exist. These include diffusion-weighted imaging (DWI) [ 105 ], magnetic transfer imaging (MTI) [ 106 ], magnetic resonance angiography (MRA) [ 107 ], magnetic resonance spectroscopy (MRS) [ 108 ], diffusion tensor imaging (DTI) [ 109 ], and blood oxygen level-dependent functional MRI (BOLD-fMRI) [ 93 ], and they ideally could be implemented for identifying functional hallmarks of NPSLE and allow its diagnosis [ 11 , 110 ]. These methods are not detailed here, as this review rather focuses on data obtained in preclinical research performed on murine NPSLE models.…”
Section: Neuroimaging In Npslementioning
confidence: 99%